80 A PILOT POPS SERVICE (PERI-OPERATIVE CARE OF THE OLDER PERSON UNDERGOING SURGERY): A PROMISING START. (25th October 2022) - Magee, M; Leung, S
Abstract: Background: It is understood that older persons undergoing surgery benefit from Comprehensive Geriatric Assessment (CGA), however these services remain limited in Ireland. Latest guidelines recommend all patients over 65 undergoing surgery should be screened for frailty and receive a CGA if frailty is identified. Our pilot service was to implement this on our acute surgical in-patient ward. Methods: Baseline data was gathered prior to implementation of our service. Interventions included education, dedicated sessions for geriatrician input on ward, single point of referral and increased signage. Patients identified as living with frailty (Rockwood Clinical Frailty Score (CFS) ≥5) then received CGA. Progress monitored with monthly audit and foundation doctor feedback surveys over a 6-month period. Results: We have increased the percentage of patients over 65 being screened for frailty from 0% to a peak of 100% over our pilot 6-month period. Foundation doctor surveys showed an improvement in confidence in screening for frailty (19 to 100%) and managing frailty (13 to 80%). They also reported feeling more supported managing these patients (38% to 100%). Focusing on patients with CFS ≥5, we have shown a reduction in length of stay from a mean of 20 days to 11 days, albeit numbers remain small. Conclusion: By increasing identification of frailty in older patients, we have managed to apply CGA to appropriate patients. Geriatrician input on the surgical ward has also allowed foundation doctors to feel supported and improve confidence in managing patients living with frailty. Furthermore, we have shown a trend towards reduced length of stay. However, our patient numbers remain low and there is a reliance on our team to screen all patients over 65. Our focus moving forward is for the surgical team to screen for frailty allowing us to expand the service to other surgical wards.